Performance evaluation of collision avoidance schemes in ad hoc networks. Issue 9 (10th March 2014) - Bhandare, Suryakant; Brahim, Taha Ben; Biaz, Saad; Agrawal, Prathima
Abstract: IEEE 802.11 distributed coordination function (DCF) is a popular protocol used for the physical and medium access control layers in most ad hoc networks. DCF employs carrier sense multiple access with collision avoidance and a binary slotted exponential back off. It has been observed that the hidden and exposed terminal problems among stations degrade DCF's performance in terms of throughput and fairness. Hence, the effectiveness of the IEEE 802.11 DCF mechanism in ad hoc networks has attracted many research studies. Many collision avoidance schemes were proposed to address the IEEE 802.11 DCF weaknesses as the performance of the medium access control layer directly impacts the performance of higher‐layer protocols and hence the entire network. An evaluation of representative schemes under the same conditions will be helpful in understanding the limitations and strengths of these schemes. This paper surveys various collision avoidance schemes, classify them on the basis of their mechanism, and then provide a comparative study of representative schemes based on their performance. They are evaluated on a chain topology, a pair topology, and a random topology with static environment to measure their throughput, fairness, collision probabilities, and delay. On the basis of the evaluation, we conclude that gentle DCF is the best scheme that has lesser collisions with improved throughput and fairness. A comparison with the legacy carrier sense multiple access with collision avoidance suggests that these proposed schemes do tend to be promising and would inspire future researchers who are interested to find solutions to the age‐old collision and fairness issues in ad hoc networks. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : This paper surveys, evaluates, and compares representative schemes aimed to improve IEEE 802.11 distributed coordination function fairness in the presence of hidden and exposed terminals.